Constructing of Restorative Justice Law Enforcement by the Prosecutor: Development Law Theory Perspective - Pratama, Ganiviantara (Pancasila and Law Review, 2022)
The development and dynamics of society, including law enforcement in Indonesia, are highly complex. Key challenges include prison overcrowding, the handling of minor offenses, legal action involving children, and narcotics issues. Restorative Justice offers a potential solution to these legal problems. This paper employs a normative juridical approach, utilizing both a conceptual and a statutory approach, and is presented from a qualitative descriptive perspective. The findings highlight the critical role of Restorative Justice in the Indonesian criminal justice system and examine how the Prosecutor's Office can implement social engineering through Restorative Justice. The proactive role of the Prosecutor's Office is anticipated to foster a more humane institution and enhance its reputation as a law enforcement agency committed to integrity.